1997
DOI: 10.2139/ssrn.15076
|View full text |Cite
|
Sign up to set email alerts
|

Productivity Growth, Technology Progress, And Efficiency Change in Chinese Agricultural Production From 1984 to 1993

Abstract: The analyses and views reported in this paper are those of the author. They are not necessarily endorsed by the Department of Agriculture or by North Dakota State University. North Dakota State University is committed to the policy that all persons shall have equal access to its programs, and employment without regard to race, color, creed, religion, national origin, sex, age, marital status, disability, public assistance status, veteran status, or sexual orientation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Due to it features and merits, a lot of literatures have used the Malmquist productivity indexes in DEA. A few of those studies are Fare, Grosskopf, Norris & Zhang (1994) which used this model to analyse the productivity comparison between countries, while Tauer & Lordkipanidze (1999) and Koo & Mao (1996) used this approach to examine economic sectors such as agricultural sector. (Alam & Sickles, 1997) used this approach to examine productivity efficiency of airlines.…”
Section: Data Envelopment Analysismentioning
confidence: 99%
“…Due to it features and merits, a lot of literatures have used the Malmquist productivity indexes in DEA. A few of those studies are Fare, Grosskopf, Norris & Zhang (1994) which used this model to analyse the productivity comparison between countries, while Tauer & Lordkipanidze (1999) and Koo & Mao (1996) used this approach to examine economic sectors such as agricultural sector. (Alam & Sickles, 1997) used this approach to examine productivity efficiency of airlines.…”
Section: Data Envelopment Analysismentioning
confidence: 99%
“…To address this, the paper employs a dynamic analysis, using DSBM and TFAE to analyze China's food production issues, and provides some recommendations for China's agricultural policies. To gather the literature related to agricultural production efficiency, productivity changes, and other relevant studies, the following steps were taken: Previous studies have found that important factors affecting agricultural productivity in Asian countries include scientific and technological progress [1][2][3][4][5], taxation [6], and capital investment [7]. The main factors affecting agricultural efficiency include machinery and fertilizer inputs [6,[8][9][10][11][12], energy use [8][9][10][11][12][13][14][15][16], irrigation infrastructure [16,17], agricultural machinery [18], and pesticides [19].…”
Section: Introductionmentioning
confidence: 99%